Possible Hepatoprotective Effect of Tocotrienol-Rich Fraction Vitamin E in Non-alcoholic Fatty Liver Disease in Obese Children and Adolescents - Al-Baiaty, Farah D.R.; Ismail, Aziana; Abdul Latiff, Zarina; Muhammad Nawawi, Khairul Najmi; Raja Ali, Raja Affendi; Mokhtar, Norfilza Mohd (Frontiers in Pediatrics, 2021)
Obesity has become a worldwide health concern among the pediatric population. The prevalence of non-alcoholic fatty liver disease (NAFLD) is growing rapidly, alongside the high prevalence of obesity. NAFLD refers to a multifactorial disorder that includes simple steatosis to non-alcoholic steatohepatitis (NASH) with or devoid of fibrosis. NAFLD is regarded as a systemic disorder that influences glucose, lipid, and energy metabolism with hepatic manifestations. A sedentary lifestyle and poor choice of food remain the major contributors to the disease. Prompt and timely diagnosis of NAFLD among overweight children is crucial to prevent the progression of the condition. Yet, there has been no approved pharmacological treatment for NAFLD in adults or children. As indicated by clinical evidence, lifestyle modification plays a vital role as a primary form of therapy for managing and treating NAFLD. Emphasis is on the significance of caloric restriction, particularly macronutrients (fats, carbohydrates, and proteins) in altering the disease consequences. A growing number of studies are now focusing on establishing a link between vitamins and NAFLD. Different types of vitamin supplements have been shown to be effective in treating NAFLD. In this review, we elaborate on the potential role of vitamin E with a high content of tocotrienol as a therapeutic alternative in treating NAFLD in obese children.